2019
DOI: 10.2109/jcersj2.18172
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen pumping based on <i>c</i>-axis-oriented lanthanum silicate ceramics: challenge toward low operating temperature

Abstract: A new electrochemical oxygen separation pump was developed by using c-axis-oriented La 9.66 Si 5.3 B 0.7 O 26.14 (c-LSBO), which has high oxide-ionic conductivity (>10 ¹3 S cm ¹1) up to 300°C. Interfacial resistance between the electrode and c-LSBO was investigated to realize the full potential of LSBO as an oxygen separation material. The formation of a Sm-doped CeO 2 (SDC) thin film (thickness: 300 nm) between the electrode and c-LSBO was effective for suppressing the interfacial resistance. Furthermore, a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 13 publications
(12 reference statements)
0
8
0
Order By: Relevance
“…The O4 sites exist along a linear path along the c -axis, so oxide ions at the O4 site are the primary conduction path in apatite-structured materials. Because of the high oxide-ion conductivity, when apatite-type LSO is applied to the solid electrolyte in electrochemical devices such as intermediate-temperature SOFCs, oxygen-separation membranes, and gas sensors, , the operating temperature can be expected to be lowered to values below 873 K. There are two strategies to improve the oxide-ion conductivity of this material. One is elemental substitution into the La and Si sites.…”
Section: Introductionmentioning
confidence: 99%
“…The O4 sites exist along a linear path along the c -axis, so oxide ions at the O4 site are the primary conduction path in apatite-structured materials. Because of the high oxide-ion conductivity, when apatite-type LSO is applied to the solid electrolyte in electrochemical devices such as intermediate-temperature SOFCs, oxygen-separation membranes, and gas sensors, , the operating temperature can be expected to be lowered to values below 873 K. There are two strategies to improve the oxide-ion conductivity of this material. One is elemental substitution into the La and Si sites.…”
Section: Introductionmentioning
confidence: 99%
“…38,39 Therefore, it can be inferred that the n-type MIEC formed in situ causes a drastic increase in the oxygen permeation flux at high applied voltages. We previously reported that the formation of an SDC interlayer with an isotropic oxide-ion conduction pathway enhanced the oxygen incorporation into c-LSBO from the triple phase boundary (TPB), 32) as shown in Fig. 5.…”
Section: Resultsmentioning
confidence: 89%
“…30,31 Additionally, by employing c-LSBO in a novel oxygen separation device and gas sensor, our group demonstrated lowto-intermediate temperature operability. 32,33 In terms of the oxygen pumping properties, cell resistance decreased by more than 80% at a DC voltage of 2.0 V upon the inclusion of an intermediate Sm0.2Ce0.8O2 (SDC) thin film layer between the c-LSBO electrolyte and the Pt electrode, compared with that of the cell without the SDC. Furthermore, using a p-type oxide-based MIEC, La0.6Sr0.4Co0.78Ni0.02Fe0.2O3 electrode, a high oxygen permeation flux of 3.5 mL cm −2 min −1 was achieved at 600 °C and a DC voltage of 1.5 V. 32 Further improvements in the oxygen pumping properties at low temperatures will significantly contribute to the realization of on-site oxygen supply and electrolysis technology.…”
Section: Introductionmentioning
confidence: 99%
“…18) On the basis of reaction Eqs. (8) and (9), we speculate that small amounts of SrO and GeO 2 have a small effect on the oxygen vacancies in La 2 O 3 . The second pathway to the introduction of oxygen vacancies is the formation of nonstoichiometric La 2 O 3 during sintering.…”
mentioning
confidence: 76%